Complementaridade quântica nos processadores quânticos da IBM - Chrysosthemos, Diego Samuel Starke (2023)
Bohr’s principle of complementarity, after gaining contributions from several researchers, moved from a qualitative analysis to a quantitative analysis through what we call today complementarity relations (CR). This change made it possible to quantify aspects of path superposition and distinguishability (predictability and entanglement) in a single experimental apparatus, for example, the Mach-Zehnder interferometer (MZI), gaining historical appeal in the quantification of path superposition through interferometric visibility. Furthermore, CR of quantum coherence, predictability and entanglement functions that are dependent on the quantum state, have also gained relevance in this area of research. In this dissertation, based on other research, we were directed to carry out two works involving the IMZ and analysis through CR. In the first work, we build a version of the MZI and show that interferometric visibility is not always able to correctly quantify the path superposition within the MZI for two-path systems. We found that CR involving quantum coherence end up reflecting the expected behavior for the photon in this same experimental apparatus. In the second work, we performed an integral analysis, through the complete CR, of the entangled quantum eraser (EQE). In this experimental apparatus, we consider a variable partially-polarizing beam splitter (VPPBS) that can produce path superposition of the horizontal and vertical polarizations entering the MZI. Due to the inclusion of the VPPBS, part of the experimental apparatus of the standard quantum eraser was modified, so that we need to perform Bell’s basis measurements of the degree of freedom of the polarizations of the two entangled photons. Therefore, the analysis of the EQE, through the CR, ends up being much richer, producing situations where there are even partial erasures of the information available before the erasure process. In both papers, we verified our theoretical findings by implementing experiments on IBM’s quantum computers.